Social Participation as a goal of the post-stroke rehabilitation program: a literature review - Souza, Felipe Heylan Nogueira de; Filho, Edson Meneses da Silva; Cezarino, Leandro Gonçalves; Melo, Egmar Longo Araújo de; Cacho, Ênio Walker Azevedo (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: Stroke is considered one of the leading causes of long-term disability worldwide. Physical, cognitive and psychological disabilities resulting from stroke can lead to a wide variety of activity limitations and participations restrictions. Objective: To verify the incidence of articles in the literature that used physiotherapy programs aimed at social participation and to analyze if these programs are based on domains of the International Classification of Functioning Disability and Health (ICF) in post-stroke people. Method: It was selected any type of study that presented post-stroke human sample over 18 years of age with no gender restriction, to be written in any language and year of publication, to have used physical rehabilitation as a form of treatment and social participation assessed by ICF as outcome. The descriptors and Boolean operators: stroke, rehabilitation, International Classification of Functioning Disability and Health, social participation, were used in the sample search strategy in database PEDro, PubMed, Web of Science and Scielo. Results: After applying the inclusion/exclusion criteria, five articles remaining. Assessment tools for participation in daily and social activities were not consensual in the range of areas that needed to be addressed in stroke rehabilitation. A single study used the ICF-based design model in its program. Conclusion: There are few studies that have measured the various characteristics of social participation using the ICF as a tool. More studies are needed to create an ideal standardization and strategy that direct interventions to improve specific aspects of social participation, including the involvement in activities that provide post-stroke individuals interaction with society.